Re-design Logo Green Futsal Balai Baru Kota Padang - NAZARUWIL, Jupriani, Ismanadi Uska (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
AbstractThis invention aims to re-design Green Futsal logo in order to make the logo of Green more unique in performance, interesting and acces the identity of Green Futsal then trading mark evaluation by the visitors. Because of the present logo is universal in use by futsal ground in Padang city. The benefits re-design is to get the uniquely and differentiate of the logo among other fulsal ground, in order to get more visitor in the future time. Because of the problems above, it is required to re-design Green Futsal logo and apply it with other supporting media.Keyword: Re-design, Logo, Green Futsal.